Resistance to negative online information of bank brands from consumer attitudes - Otero-Gómez, María Cristina; Giraldo-Pérez, Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The aim of this manuscript is to explain the incidence of cognitive and affective attitudes in the resistance to negative information circulating in the online environment about banks in Colombia. Information was collected from a sample of 282 bank users. The data were analyzed using IBM SPSS Statistics V.25 software. The cognitive attitude was measured from the service experience scales and the affective attitude considered the brand love items. The results suggest that both cognitive and affective dimensions promote resistance to negative information, however, it is the rational component that has a stronger positive effect compared to the emotional component. It is concluded that when consumers have positive experiences in service delivery, they are reluctant to the influence of negative comments that may diminish the bank's image.